Safe Educational Environment as a Priority of Personality Socialization in Modern Realities - Tang, Xishun (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The article highlights the key challenges facing contemporary Ukrainian society, underscoring the need to ensure a safe educational environment. The role and significance of such an environment are emphasized as strategic priorities for socializing individuals, fostering civic responsibility, and maintaining learners’ psychosocial well-being. An analysis of regulatory documents governing the creation and functioning of a safe environment in educational institutions is conducted, with particular attention to their substantive focus and practical orientation. The aim of the article is to investigate the theoretical foundations and practical aspects of forming a safe educational environment as a key factor in the development of modern educational institutions. The study employs methods of theoretical analysis of national and international scholarly works, examination of regulatory documents, analysis, synthesis, generalization, systematization, and the method of scientific transfer – applying theoretical provisions to educational practice. The approaches of foreign and domestic researchers who conceptualize the educational environment as a crucial component in shaping an individual's educational trajectory and developing learners' personal potential are examined. It is established that the structure and quality of the educational environment are determined by the interaction of external (social, informational, and security-related) and internal (organizational, pedagogical, and psychological) factors. The key conditions for the formation and development of a safe educational environment are outlined, and the principles underlying its functioning amid contemporary socialization challenges are identified. The provisions of the Concept of a Safe Educational Environment and the Code of a Safe Educational Environment which constitute the regulatory basis for safety assurance in education are analyzed. An authorial interpretation of the term “safe educational environment” is proposed, taking into account contemporary approaches to pedagogical, social, informational, and physical safety. The ecological dimension of safety and the informational components of the educational space are considered, with emphasis on their impact on the quality of the educational process and participants' psychological comfort during educational interaction.